Transcriptomic analysis and experiments revealed that remimazolam promotes proliferation and G1/S transition in HCT8 cells - Wang, Runjia; Li, Shuai; Hu, Han; Hou, Qi; Chu, Huaqing; Hou, Yu; Ni, Cheng; Ran, Yuliang; Zheng, Hui (Frontiers in Oncology, 2024)
Background: Remimazolam is a new ultrashort-acting benzodiazepine for sedation and anesthesia. The effects of remimazolam and the mechanism by which it functions in cancer cells have not been determined. This research aimed to explore the mechanism of remimazolam action in colon cancer treatment, using bioinformatics analysis and in vitro experiments. Methods: Cell cycle progression, colony formation, self-renewal capacity and apoptosis detection were performed in HCT8 cells treated with or without remimazolam. Transcriptome sequencing, Gene Ontology, Kyoto Encyclopedia of Genes and Genome, Protein-Protein Interaction, Gene Set Enrichment Analysis, Western blotting and qPCR were performed to investigate the mechanism of action of remimazolam in HCT8 colon cancer cells. Results:Remimazolam promoted proliferation and cell cycle progression of HCT8 cells. After remimazolam treatment, a total of 1096 differentially expressed genes (DEGs) were identified, 673 genes were downregulated and 423 genes were upregulated. The DEGs were enriched mainly in "DNA replication", "cell cycle" and "G1/S transition" related pathways. 15 DEGs were verified by qPCR and representative biomarkers were detected by Western blotting. The remimazolam-mediated promotion of cell proliferation and cell cycle was reversed by G1T28, a CDK4/6 inhibitor. Conclusion: Remimazolam promoted cell cycle progression and proliferation in HCT8 colon cancer cells, indicating that the long-term use of remimazolam has potential adverse effects in the anesthesia of patients with colon cancer.